Analisis Faktor-Faktor Penentu Upah Minimum Regional Menggunakan Regresi Linear Berganda - Manik, Indri Theresia; Saldi, Aqil Afrizqal; Junita, Iqva; Sitorus, Nadicta Eunike; Sagala, Regilpa; Pinem, Yoga Nawarisa (Griya Journal of Mathematics Education and Application, 2025)
This study analyzes the factors influencing the determination of the Regional Minimum Wage (UMR) in Indonesia in 2024 using multiple linear regression. The variables used include the Living Needs (KHL), Gross Domestic Product/Gross Regional Domestic Product (GDP/GRDP), and labor productivity. Data were obtained from the Central Statistics Agency (BPS) and the Ministry of Manpower of the Republic of Indonesia, covering 20 provinces after data cleaning from outliers. The results show that the KHL has a very significant and positive effect on the UMR, meaning that the higher the cost of living in a province, the higher the UMR set. GDP also has a positive effect, indicating that a region's economic capacity increases the minimum wage. Conversely, labor productivity has a negative effect on the UMR, indicating that regions with high productivity tend to have lower wage levels due to labor market dynamics. These findings emphasize the importance of considering socio-economic factors that vary across regions in formulating minimum wage policies in Indonesia.